(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this manuscript, we used the supra soft interior operator to define a new approach of generalized sets named, supra soft somewhat (briefly, SS-sw-) open sets. We discuss its relationships with the other generalizations and provide the necessary examples and counterexamples. After that, we define new continuity inspired by this new approach, named SS-sw-continuous function. We characterize several of its essential properties. We use the SS-sw-closure (interior) operators to present several equivalent conditions for the new approach. Furthermore, we define a new type of functions related to SS-sw-open sets, named SS-sw-open functions.